Answer:(k+1)(2K+7)
Step-by-step explanation:
Using the quadratic formula
X=-b±-√b^2-4ac/2a
ax^2+bx+c=0
2k^2+9k+7=0
In this case a=2,b=9,c=7
-9+-√9^2-4(2)(7)/2(2)
(-9+√25)/4=-9+5/4=-1
(-9-√25)/4=-14/4 =-7/2
X=-1,X=-7/2
So (K+1)(k+7/2)
So (k+1)(2k+7)
Answer:
0.1254
Step-by-step explanation:
(Divide by 100 to get 1%)
420 bagels in 14 hours, and they made 30 bagels per hour
All you have to do is divide 300 by 10 to get you bagels per hour
Step-by-step explanation:
3(2x - 3) - 4(2x + 1) <= 26
-2x - 13 <= 26
2x <= -39
x <= -19.5.
You write it as a improper fraction first*
20
-----
8
and then u divide 8 into 20
and we know that it goes in it 2.5 times
so simply from here
it is 2.5%